Brazil, 1964-1985 the military regimes of Latin America in the Cold War - Klein, Herbert S.; Luna, Francisco Vidal (Yale University Press, 2017)
Comparing and contrasting the history, programs, methods, and goals of Brazil's Cold War-era authoritarian government with the military regimes of Peru, Chile, Argentina, Bolivia, and Uruguay, authors Herbert Klein and Francisco Vidal Luna offer a fascinating, detailed analysis of the Brazilian experience from 1964 to 1985, one of the darkest, most difficult periods in Latin American history.